2018
DOI: 10.1038/s41598-018-30422-9
|View full text |Cite
|
Sign up to set email alerts
|

Cortical signatures of wakeful somatosensory processing

Abstract: Sensory inputs carry critical information for the survival of an organism. In mice, tactile information conveyed by the whiskers is of high behavioural relevance, and is broadcasted across cortical areas beyond the primary somatosensory cortex. Mesoscopic voltage sensitive dye imaging (VSDI) of cortical population response to whisker stimulations has shown that seemingly ‘simple’ sensory stimuli can have extended impact on cortical circuit dynamics. Here we took advantage of genetically encoded voltage indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 63 publications
(85 reference statements)
3
54
0
1
Order By: Relevance
“…Swiss Webster mice of either sex were used for the isolation of primary neurons [animal age, postnatal day 0.5 (P0.5)], as well as for the intracerebroventricular injections of genetically encoded voltage indicators packed in several variants of adeno-associated virus (AAV) backbones (animal ages, P0–P1), according to the animal protocols approved by the UConn Health Institutional Animal Care and Use Committee. For the evaluation of chimeric voltage-sensitive fluorescent protein (chi-VSFP), we used transgenic animals (C57BL/6 background) that express chi-VSFP ( Song et al, 2017 , 2018 ) in all cortical pyramidal neurons (CaMK2A-tTA; chi-VSFP), which were donated by Chenchen Song and Thomas Knöpfel (Imperial College London).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Swiss Webster mice of either sex were used for the isolation of primary neurons [animal age, postnatal day 0.5 (P0.5)], as well as for the intracerebroventricular injections of genetically encoded voltage indicators packed in several variants of adeno-associated virus (AAV) backbones (animal ages, P0–P1), according to the animal protocols approved by the UConn Health Institutional Animal Care and Use Committee. For the evaluation of chimeric voltage-sensitive fluorescent protein (chi-VSFP), we used transgenic animals (C57BL/6 background) that express chi-VSFP ( Song et al, 2017 , 2018 ) in all cortical pyramidal neurons (CaMK2A-tTA; chi-VSFP), which were donated by Chenchen Song and Thomas Knöpfel (Imperial College London).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we found that Archon1 (red emission) and ASAP3b (green emission) are suitable for monitoring fast action potentials in individual cells, with ASAP being a slightly brighter and more forgiving probe. Our current data are potentially useful for guiding the practical choice of a GEVI indicator depending on the following: (1) biological application (e.g., cell body action potential; Abdelfattah et al, 2019); cell body UP state-a sustained ;20 mV depolarization (Adam et al, 2019;Villette et al, 2019), dendritic back-propagating action potential (Gong et al, 2015;Adam et al, 2019), dendritic subthreshold depolarization (Kwon et al, 2017), compound excitatory synaptic potential (Storace and Cohen, 2017;Song et al, 2018), and compound inhibitory (hyperpolarizing) synaptic potential (Nakajima and Baker, 2018);…”
Section: Introductionmentioning
confidence: 99%
“…However, there are currently a limited number of transgenic mice expressing GEVIs with high signal-to-noise ratios (Butterfly 2.1 [21], QuasAr2 [22], ASAP2s [23]), and even fewer studies showing their utility in vivo [24,25]. Here we took advantage of a novel transgenic reporter mouse, Ai86(TITL-ArcLight) [21,23], that can be used to selectively drive expression of the GEVI ArcLight [7] in specific cell types.…”
Section: Introductionmentioning
confidence: 99%
“…The development of CRISPR/Cas9 genome editing technologies significantly improved and simplified the development of new transgenic mouse lines [353][354][355]. Many lines expressing GEFIs in the brain already exist [28,30,[356][357][358][359][360][361][362]; in addition, a number of lines express GEFIs in a Cre recombinase-dependent manner and can be bred into distinct Cre recombinase driver mice to direct expression of sensors in the selected cell populations [363]. Some transgenic lines are commercially available (jax.org).…”
Section: Animal Models For Real-time Imaging Of Cell Signaling and Mementioning
confidence: 99%